Adenylation Domains in Nonribosomal Peptide Engineering. (13th March 2019) - Stanišić, Aleksa; Kries, Hajo
Abstract: Nonribosomal peptides are a prolific source of bioactive molecules biosynthesized on large, modular assembly line synthetases. Synthetic biologists seek to obtain tailored peptides with tuned or novel bioactivities by engineering modules and domains of these nonribosomal peptide synthetases. The activation step catalyzed by adenylation domains primarily selects which amino acids are incorporated into nonribosomal peptides. Here, we review experimental protocols for probing the adenylation reaction that are applicable in natural product discovery and engineering. Several alternatives to the established pyrophosphate exchange assay will be compared and potential pitfalls pointed out. Binding pocket mutagenesis of adenylation domains has been successfully conducted to adjust substrate preferences. Novel screening methods relying on yeast surface display, for instance, search a larger sequence space for improved mutants and thus allow more substantial changes in peptide structure. Abstract : Tinker, tailor : Nonribosomal peptide synthetases are large, modular enzymes responsible for the biosynthesis of numerous bioactive molecules. Great efforts are invested in exploiting these enzymes as a source of tailored peptides. This Minireview covers experimental approaches for probing the activity of the "gatekeeper" adenylation domain alongside strategies for engineering.